2021
DOI: 10.1073/pnas.2105739118
|View full text |Cite
|
Sign up to set email alerts
|

Design and proof of concept for targeted phage-based COVID-19 vaccination strategies with a streamlined cold-free supply chain

Abstract: Development of effective vaccines against coronavirus disease 2019 (COVID-19) is a global imperative. Rapid immunization of the entire human population against a widespread, continually evolving, and highly pathogenic virus is an unprecedented challenge, and different vaccine approaches are being pursued. Engineered filamentous bacteriophage (phage) particles have unique potential in vaccine development due to their inherent immunogenicity, genetic plasticity, stability, cost-effectiveness for large-scale prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 75 publications
(111 reference statements)
1
31
0
Order By: Relevance
“…A noninfectious phage T4-CoV-2 vaccine with no tropism to human cells and no use of adjuvants or chemical stimulants represent significant advantages. Two recent phage-COVID vaccine studies using filamentous AAVP ( 71 ) and Bxb1 phage ( 24 ) also demonstrated the advantages of phage vaccine system, including the low cost of production, the self-adjuvanted nature, and the strong safety profile. In fact, our previous studies showed that adding adjuvants such as alum or liposomes did not further enhance the levels of immune responses ( 20 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…A noninfectious phage T4-CoV-2 vaccine with no tropism to human cells and no use of adjuvants or chemical stimulants represent significant advantages. Two recent phage-COVID vaccine studies using filamentous AAVP ( 71 ) and Bxb1 phage ( 24 ) also demonstrated the advantages of phage vaccine system, including the low cost of production, the self-adjuvanted nature, and the strong safety profile. In fact, our previous studies showed that adding adjuvants such as alum or liposomes did not further enhance the levels of immune responses ( 20 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages vaccination is an innovative and novel vaccine system. 25,26 This is a bio-engineered structure that entails a DNA vaccine contained within a phage capsule under the expression of a eukaryotic promoter. 21 Once the phage transporting the DNA vaccine is engulfed into a eukaryotic antigen-presenting cell, the vaccine gene is expressed.…”
Section: Bacteriophage Vaccinationmentioning
confidence: 99%
“…Another interesting application of phage display related to medicine is their proven role as vaccines at pre-clinical level [ 64 ]. Phage display is used to display viral or bacterial antigenic peptides on phage capsids followed by in vivo administration to induce an immune response [ 77 , 78 ]. Due to the inherent ability of phages to induce balanced innate and adaptive immunity, phage vaccines are shown to impart better synergistic immune response when compared to free subunit antigens, without the use of adjuvants [ 79 ].…”
Section: Amenable Phage Featuresmentioning
confidence: 99%